(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research problem consisted in answering the question that revolves around whether there is a relationship to the settlement of salaries with the growth of bank deposits? The research also aimed to provide some initial solutions to improve the role of salary localization, in terms of reviewing the concept of electronic payment systems, its tools and channels, and then identifying the concept of salary localization, its importance, objectives and obstacles to its application, and then analyzing the reality of the state of the settlement of salaries and bank deposits for the research sample banks, which are each of the bank (Ashur International, Business Bay, the Iraqi Middle East for Investment, the Iraqi National, Development and the Iraqi Islamic Bank for the period (2017- 2021), and the use of the statistical program (SPSS V25) by paying attention to the value of the statistical significant correlation coefficient (p_value), in testing the research hypotheses. The study relied on the inductive approach and the descriptive analytical method in the study and analysis of information and data in the available literature on research concepts, methods of measuring it to determine the level of salary localization, and analysis of bank deposit data. The study found a set of results, the most important of which are: There is a significant correlation (statistically significant) between the variable (number of domiciliation accounts) and the variable (the size of bank deposits), where the correlation coefficient between them reached (0.95), which is a strong and significant direct correlation coefficient (statistically significant) below the level of Significant (0.01) on the total level of the six banks in the study sample.